PROFIL KIMIA ARTOCARPUS - Erwin - (JURNAL KIMIA MULAWARMAN, 2010)
Artocarpus, one of the main genus of  Moraceae is known as a rich source of phenolic compounds especially prenylated flavonoids with a variety of structural types. From the literature review we obtained some phenolic compounds such as  calkon, flavane, flavone, Santon, stilben and Adduct Diels-Alder Type. Keywords: Artocarpus, phenolic, flavon